2007
DOI: 10.1007/s10484-007-9030-1
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Electroencephalographic Correlate of Sustained Attention Processing

Abstract: The objective of the present investigation was to develop a quantitative electroencephalographic measure (qEEG) that is sensitive and specific to changes in sustained human performance. A principal components analysis (PCA) was performed on the qEEG obtained from participants during a continuous performance test. Measures of sensitivity (proportion of correctly identified correct responses, or hits) and specificity (proportion of correctly identified incorrect responses, or misses) were calculated to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
1
6
0
1
Order By: Relevance
“…Periodicities ranging from 1.00 to 2.00 min and from 4.70 to 5.70 min with amplitudes greater than would be expected due to chance were retained (Smith et al 2003). The results of the present investigation validate the existence of cyclic variations in human performance that have been identified previously (Smith et al 2003) and extend those findings by implicating right-hemisphere mediated arousal in the process (Arruda et al 1996(Arruda et al , 1999(Arruda et al , 2007. Significant cyclic variations in left-hemisphere betawave activity were not observed.…”
supporting
confidence: 85%
See 3 more Smart Citations
“…Periodicities ranging from 1.00 to 2.00 min and from 4.70 to 5.70 min with amplitudes greater than would be expected due to chance were retained (Smith et al 2003). The results of the present investigation validate the existence of cyclic variations in human performance that have been identified previously (Smith et al 2003) and extend those findings by implicating right-hemisphere mediated arousal in the process (Arruda et al 1996(Arruda et al , 1999(Arruda et al , 2007. Significant cyclic variations in left-hemisphere betawave activity were not observed.…”
supporting
confidence: 85%
“…Absolute power in the beta frequency range (12-25 Hz) was then calculated for each of the 1,800 segments using a Fast Fourier Transformation (FFT) algorithm introduced by Brigham (1974), producing a near continuous 30 min record of absolute beta power for each of the 58 active electrode recording sites. Absolute beta power measured from four unipolar recording sites (i.e., F8, C6a, C6, and T4) was then averaged to form a single right-hemisphere composite variable that has proven to be both sensitive and specific to changes in sustained human performance (Arruda et al 2007). The beta frequency bandwidth and the EEG recording sites used were selected to closely approximate that used by Arruda et al (1996Arruda et al ( , 1999Arruda et al ( , 2007.…”
Section: Scan Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Line bisection is a spatial task that requires the use of Vertical scanning 107 global (vs. focal) attention and requires continuous (vs. categorical) processing. Studies in normal subjects have demonstrated that it is the right hemisphere that is dominant for global attention (Robertson et al, 1988), continuous processing (Arruda et al, 1996(Arruda et al, , 2007, and spatial computations (Jager & Postma, 2003). Thus, when performing the routine line bisection task, normal subjects should initially orient to the left side of the line.…”
Section: Discussionmentioning
confidence: 99%